Genomic Diversity Analysis Reveals a Strong Population Structure in Histoplasma capsulatum LAmA (Histoplasma suramericanum) - Fernando Almeida-Silva; Marcus de Melo Teixeira; Daniel R. Matute; Marcela de Faria Ferreira; Bridget M. Barker; Rodrigo Almeida-Paes; Allan J. Guimarães; Rosely M. Zancopé-Oliveira (Journal of Fungi, 2021)
Histoplasmosis is a severe mycotic disease affecting thousands of immunocompetent and immunocompromised individuals with high incidence in Latin America, where the disease agents are Histoplasma capsulatum and Histoplasma suramericanum. In this work, we used whole-genome sequencing to infer the species diversity and the population structure of H. suramericanum in South America. We find evidence for strong population structure and little admixture within the species. Genome-level phylogenetic trees indicate the existence of at least three different discrete populations. We recovered the existence of a previously identified population, LAmB, and confirm that it is highly differentiated along the whole genome. We also find that H. suramericanum is composed of two populations, one in Northern South America, and another in the southern portion of the continent. Moreover, one of the lineages from the southern population is endemic to Rio de Janeiro and there was no association with clinical data and species isolated from patients with histoplasmosis. Our results point out the need to characterize the symptomatology of histoplasmosis caused by different species and lineages of Histoplasma spp.